Anti- Schistosomular Activity of Human Monocytes/Macrophages in Response to Interleukin-3 and Granulocyte-Macrophage Colonystimulating Factor Stimulation - D. Gold; L. Nissimov; J. Lengy; Y. Keisari (Mediators of Inflammation)
Human monocytes, co-incubated for 7 days in culture with GM-CSF or IL-3 but not with IFN-γ, exerted a variable schistosotnulicidal effect on Schistosoma mansoni parasites when grown in 96-well round-bottomed plates but not in flat-bottomed plates. Addition of LPS or IFN-γ or both, for the last 48 h did not enhance the cidal effect. Addition of LPS but not IFN-γ to the pre-incubated cells with GM-CSF or IL-3 markedly stimulated TNF-α production by the cells but not their cidal activity. The variable cidal effects obtained with the monocytes/macrophages from different donors suggest that these effects may be genetically predetermined and are possibly linked to blood group markers or to MHC class I or II antigens.